The radial limits and boundary uniqueness - Danielyan, Arthur (Comptes Rendus. Mathématique)
The paper sheds a new light on the fundamental theorems of complex analysis due to P. Fatou, F. and M. Riesz, N. N. Lusin, I. I. Privalov, and A. Beurling. Only classical tools available at the times of Fatou are used. The proofs are very simple and in some cases – almost trivial.